Review of epidemiological and clinical characteristics and overall survival in patients with colorectal cancer - Michelle Eisenhardt (Universidade de Santa Cruz do Sul, 2013)
Backgound and Objectives: Colorectal cancer (CRC) has high incidence, is often treatable and curable if diagnosed early. This study aimed to identify the epidemiological characteristic and assess overall survival in patients with CRC treated at a center specializing in oncology. Methods: Medical records of 127 patients with CRC were retrospectively evaluated. Clinical and epidemiological characteristics, in addition to treatment protocols and adverse reactions presented by patients were reviewed. The association of significance was assessed by chi-square and Fisher exact tests. The survival analyses were performed using the Kaplan-Meier method. The confidence interval was of 95% (p